PENGARUH EDUKASI SDIDTK MENGGUNAKAN MEDIA VIDEO DAN BOOKLET TERHADAP PENGETAHUAN KADER MELAKUKAN SDIDTK BALITA DI POSYANDU - Resty Noflidaputri; Herneli Yusana (Maternal Child Health Care, 2022)
SDIDTK activities are integrated with posyandu activities. SDIDTK is one of the flagship programs of Puskesmas. This activity was carried out by health workers comprehensively and coordinated manner with cadres oriented to KIA books. This study aims to determine the effect of SDIDTK education using videos and booklets on increasing the ability of cadres to carry out SDIDTK Toddlers at the Posyandu in the Work Area of the Bangko Health Center in 2022.This type of research is a quasi-experimental design with Pretest-Posttest. The variables studied were the knowledge and abilities of cadres. The research population was all cadres in posyandu totaling 71 people with a sample of 42 respondents with one group sample using purposive sampling technique. The instrument uses video media, booklets, questionnaires and checklist sheets. Data analysis used Paired T-test (p < 0.05).The results obtained on the average knowledge score (Pretest Mean 1.67, SD 0.477 and Posttest Mean 2.00, SD 0.000) and on the average ability score (Pretest Mean 1.67, SD 0.477 and Posttest Mean 1.98 , SD 0.154).There is an effect of video and booklet media on knowledge (p= 0.000) and ability (p=0.000). Continuous development and evaluation need to be carried out so that the skills of cadres are good and the performance of the posyandu also increases. Keywords: SDIDTK, Video Media, Booklet Media, Cadre of Posyandu, Knowledge